KINERJA PENYULUH PERTANIAN DALAM MASA PANDEMI COVID-19 DI KELURAHAN TARATARA SATU KECAMATAN TOMOHON BARAT KOTA TOMOHON - Hiskia Engelbert Tandibato; Rine ., Kaunang; Meisje Yellie Memah (Sam Ratulangi University, 2021)
This research aims to figure out about the agricultural extension workerâ€™s performance of their main tasks at Sub-district Taratara Satu, Tomohon City. The types of data used in this study are primary and secondary data obtained through direct interviews with farmers and through questionnaires. The sampling method thatâ€™s being used in this study is Purposive Sampling Method; where the researcher chooses the respondents themselves from the farmers. This research used descriptive analysis that namely explaining the data obtained by using words that are assisted by data tables. This research shows that the performance of agricultural extension workers; which can be measured from the main task of extension workers where the results tend to be good because agricultural extension activities are only focused on agricultural core activities. Such as agricultural programs, technical meetings, demonstrations, and courses for the farmers.Â